Assessment of the Quality of Drug Therapy in Patients with Stable Coronary Artery Disease in the Second Stage of the ALIGN Study - E. D. Zharkova; S. Yu. Martsevich; Yu. V. Lukina; N. P. Kutishenko; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To assess adjusted pharmacotherapy for prescribing drugs of the main classes, according to clinical guidelines, and achieving target levels of lowdensity lipoprotein cholesterol (LDL-C) in patients with stable coronary heart disease (CHD).Material and methods. Of the 73 patients included in the ALIGN study, 64 patients (53 males and 11 females; mean age 68,2±9,4 years) with stable coronary artery disease attended a second visit (3 months after the initial treatment adjustment). Prescribed drug therapy, its compliance with clinical guidelines, achievement of lipid profile and blood pressure (BP) targets were studied in all patients.Results. An increase in the frequency of taking beta-blockers (p=0.002), lipid-lowering drugs (p=0.008) by patients was found during the second visit. The proportion of patients taking all 4 groups of drugs according to clinical guidelines (statins, antiplatelet agents, beta-blockers, angiotensinconverting enzyme inhibitors / angiotensin II receptor blockers) increased from 44% to 65.5% (p<0.001) after correction of therapy, as well as an increase in the proportion of patients taking 1 antianginal drug in the presence of exertional angina from 75% to 89% (p<0.001) was found. About 90% of hypertensive patients achieved the target level of systolic blood pressure (p<0.001). Achievement of the target level of cholesterol low density lipoprotein (<1.8 mmol/l) during the second visit was found in half of the patients (p=0.004).Conclusion. Despite the initial correction of drug therapy by the staff of the cardiology department, the prescribed treatment for patients with stable coronary artery disease did not in all cases comply with clinical guidelines due to insufficient adherence of doctors and insufficient adherence of patients to prescribed medical recommendations.Working group of the register PROFILE: Voronina V. P., Dmitrieva N. A., Komkova N. A., Zagrebelny A.V., Kutishenko N.P., Lerman O.V., Lukina Yu. V., Tolpygina S.N., Martsevich S.Yu.